What you need to know about reading comprehension & speed, skimming & scanning, reading for pleasure - Coman, Marcia J. 4 0 16; 5 (Lincolnwood, IL : National Textbook, 1991)
Includes hands-on, practical activities to help the user read better, faster, and build vocabulary.
Young Adult;Young Adult
Keywords: 2 -- 0; 6; Study, Method of.;Reading.;Reading.;Study skills -- Handbooks, manuals, etc; 20; 2